PEMANFAATAN BEBERAPA TUMBUHAN LIAR (GULMA) SEBAGAI SAYURAN DI KABUPATEN JEMBER - Umiyah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
The study aims to document the wild plant (weeds) species used as vegetables, kinds of cooking and the cooking-ways by the people of Jember District. Preliminary observation carried out to dig up the information about the vegetable species used in daily life with attention the etnics uses. Furthermore, the data collection for the selected people by using semi-structured interview informally. Specimens collected were identified at Herbarium Jemberiense, Department of Biology, University of Jember. Ten wild plants (weeds) species from eight families were reported to be used as vegetables by Madurase and Javanese people in Jember. Most of the species are cooked in boiling way and serving as salad (lalapan), and the others are processed in varieties dish. Then, six species can be found in traditional markets, two of them only occasionally found. Four species left, its could be picked/taken by people on the habitat directly.